A Li+ conductive metal organic framework electrolyte boosts the high-temperature performance of dendrite-free lithium batteries. Issue 16 (4th April 2019) - Chen, Nan; Li, Yuejiao; Dai, Yujuan; Qu, Wenjie; Xing, Yi; Ye, Yusheng; Wen, Ziyue; Guo, Cui; Wu, Feng; Chen, Renjie
Abstract : Conventional electrolytes of Li metal batteries are highly flammable and volatile, which accelerates the consumption of lithium metal at high temperatures, resulting in catastrophic fires or explosions. Abstract : Conventional electrolytes of Li metal batteries are highly flammable and volatile, which accelerates the consumption of lithium metal at high temperatures, resulting in catastrophic fires or explosions. Herein, a Li + conductive metal organic framework electrolyte was prepared to enable dendrite-free Li deposition at high temperatures. This electrolyte stabilizes the electrolyte/electrode interface by promoting the transport of lithium ions and suppresses the formation of Li dendrites by forming a particle-rich coating over the anode during repeated Li plating/stripping. Benefitting from strong interactions between TFSI − anions and the metal atoms of the MOF, the electrolyte demonstrates excellent electrochemical properties, which allows Li/Li cells to operate at 150 °C for more than 1200 h without major voltage fluctuations, markedly increasing the stability of Li metal at high temperatures. Furthermore, Li/LiFePO4, LiNi0.33 Mn0.33 Co0.33 O2, Li/LiNi0.8 Mn0.1 Co0.1 O2 and Li/Li4 Ti5 O12 cells exhibit excellent performance at high temperatures.